Post-occupancy evaluation: a review of literature. Issue 9 (21st October 2019) - Roberts, C.J.; Edwards, David John; Hosseini, M. Reza; Mateo-Garcia, Monica; Owusu-Manu, De-Graft
Abstract : Purpose: The purpose of this paper is to analyse extant literature on POE of a building's operations and performance as a means of holistically mapping the existing body of knowledge (BOK); identify impediments preventing its wide-scale adoption throughout practice; and develop new theory that seeks to integrate digital technologies (such as building information modelling (BIM)) within facilities management (FM) via a POE feedback mechanism. Design/methodology/approach: An inductive and interpretivist methodological approach is adopted that utilises a mixed methods systematic review to map bibliometric data on the POE, associated underpinning processes and benchmarking facilities. Publication and citation metrics are produced via the software VOSviewer to determine the extent to which POE interrelates with other fields of study (namely, digital technologies and FM). Findings: The BOK accrued illustrates that whilst POE has received comparatively scant academic attention in comparison to other fields of study, interest in the area is growing. The work also identifies that a stronger community of practice (CoP) is needed (that comprises of academics and practitioners) to ensure that a consistent approach to POE implementation is developed and that the barriers to POE implementation are addressed. Originality/value: Findings presented accentuate the need for design practitioners to reverse engineer POE implementation to inform future design vis-à-vis simply reporting upon an existing building's performance post construction. Other new theories are also introduced as a means of engendering wider academic discourse in this field of science.